A diagnostic multiplex PCR scheme for identification of plant-associated bacteria of the genus Pantoea - Kini, K.; Agnimonhan, R.; Dossa, R.; Silué, D.; Koebnik, R. (Cold Spring Harbor Laboratory, 2018)
The genus Pantoea forms a complex of more than 25 species, among which several cause diseases of several crop plants, including rice. Notably, strains of Pantoea ananatis and Pantoea stewartii have been found to cause bacterial leaf blight of rice in Togo and Benin, while other authors have observed that Pantoea agglomerans can also cause bacterial leaf blight of rice. The contribution of these and perhaps other species of Pantoea to plant diseases and yield losses of crop plants is currently not well documented, partly due to the lack of efficient diagnostic tools.